Preschool Education and Kindergarten Teacher Training in Bulgaria and Slovakia - Rozalina Engels-Kritidis; Miriam Valášková; Róbert Osaďan (Ignatianum University Press, 2018)
While reviewing the modern theoretical framework of Bulgarian preschool education and some significant reforms in preschool  education  in Slovakia,  the  current  paper  presents  the  contemporary   situation   of preschool education in Bulgaria and Slovakia and considers  some  converging points  between  them,  but  some  differences  as  well.  Since  having   a university education for future kindergarten teachers is  influencing  their future  pedagogical  interaction  with  children,   the   university   level preparation of future kindergarten teachers is also detailed.